Determination of disassembly interference matrix and improved nondestructive disassembly sequences for the product - Mircheski, Ile (Journal of Production Engineering, 2019)
This paper presents improved method for determination of disassembly interference matrix and improved nondestructive disassembly sequences during the product evaluation stage. The main objective of the improved method for nondestructive disassembly is increasing of recycling, recovery or reuse of the components. The determination of disassembly interference matrix is based on information obtained from 3d CAD model of product and developed software package. The goal of this research is to support and help product designer to create product with improved performance in order to nondestructive disassembly and predict, evaluate and define nondestructive disassembly sequences with low costs for disassembly, minimizing of reorentation of tools in the design stage when the 3d CAD model of product is avaliable. Verification of the improved method for determination of disassembly interference matrix and improved nondestructive disassembly sequenses is presented through an illustrative example.